Auditory electrophysiology a clinical guide - Atcherson, Samuel R.; Stoody, Tina M. (Thieme, 2012)
This is a valuable contribution to any audiologist's or neuro-otologist's library. It is a complete and thorough review of the various modalities and applications in auditory electrophysiology. Its unique clinical perspective distinguishes it from most other books in this area.